Analisis Literatur Terhadap Strategi Implementasi Tari Tradisional pada Anak Usia Dini dan Efektivitasnya dalam Penanaman Nilai Budaya Regilius - Verdinata, Ismi (IIQ An Nur Yogyakarta, 2025)
Instilling religious cultural values from an early age is an important foundation in the formation of children's character and identity. One effective approach to cultural values education is through the implementation of traditional dance in learning activities in early childhood education institutions (PAUD). This study is a literature analysis that aims to examine various strategies for implementing traditional dance in early childhood learning and evaluate their effectiveness in instilling religious cultural values. The results of the study indicate that strategies involving a playful approach, integration with learning themes, and active involvement of teachers and parents can increase the effectiveness of traditional dance learning. In addition, the implementation of traditional dance has been proven to instill values such as cooperation, discipline, respect for local culture, and positive self-expression. Obstacles that often arise include limited resources, lack of teacher training, and minimal documentation of local dances appropriate for early childhood. Therefore, ongoing training for educators and collaboration with local artists are needed to support the preservation of religious culture through education. This study recommends the development of a contextual curriculum that integrates traditional dance systematically and sustainably into the learning process in PAUD. This study recommends the development of a contextual curriculum that integrates traditional dance systematically and sustainably into the learning process in PAUD.